Effect of ethanol blends, E10, E25 and E85 on sub-23 nm particle emissions and their volatile fraction at exhaust of a high-performance GDI engine over the WLTC. (1st November 2022) - Catapano, Francesco; Di Iorio, Silvana; Magno, Agnese; Sementa, Paolo; Vaglieco, Bianca Maria
Highlights: The effect of ethanol blends at 10, 25 and 85 %v/v on the emissions of sub-23 nm particles was investigated. Measure of sub-23 nm particles in transient conditions at the exhaust of a turbocharged GDI engine was performed. Evaluation of the volatile organic fraction of the sub-23 nm particles was carried out. Large volatile organic fraction in the sub-23 nm range for low cold and extra-high phases of WLTC was observed. Abstract: This study was aimed to characterize the effect of ethanol blends on sub-23 nm particles and on their volatile organic fraction from a turbocharged 1.8 L direct injection spark ignition engine. Tests were performed on the Worldwide Harmonized Light Vehicles Test Cycle. Engine was fueled with three different blends: 10, 25 and 85 %v/v of ethanol content, gasoline was used as reference fuel. An Engine Exhaust Particle Sizer was used to measure the particle number and size in the range 5.6–560 nm. Particle measure was carried out by diluting the sample gas through both a single diluter and the Dekati Engine Exhaust Diluter. The number and diameter of particles emitted from ethanol blends as well as the presence of volatiles are affected from both the specific phase of the cycle and the fuel properties. A large fraction of volatiles in the sub-23 nm range, especially in the low and extra-high phases of the test cycle, was observed whatever the fuel. Anyway, the percentage of sub-23 m particles increases as the ethanol content in the blends increases except for E85. For this blend, the greater decrease of temperature due to the stronger charge cooling effect ascribable to the larger ethanol content, deteriorates the combustion evolution contributing to the formation of large soot particles. The addition of ethanol to gasoline fuel increases the volatile organic fraction whatever the blend ratio.